Effects of Inquiry-Based Approach and Polya’s Problem Solving on Physics Achievement and Problem Solving Ability of Grade 12 Students - ดราแม อาซิ; โมพันธุ์ ณัฐินี; วิชัยดิษฐ ธิดารัตน์ (Al-HIKMAH Journal, 2018)
This research aimed to study the Effects of Inquiry-Based Approach and Polya’s Problem Solving on Physics Achievement and Problem Solving Ability of Grade 12 Students. The sample group of this research was 30 students in Grade 12/1 classroom of Grade 12 Students at Muslimpattanasart School, Yaring District, Pattani Province during the second semester of the 2014 academic year, received by purposive sampling. They were instructed for 15 hours. The research instruments consisted of lesson plans, achievement test Physics, problem - solving ability test, Satisfaction Questionnaires, the observation of students form, field note and an interview and one group pretest - posttest design. The data were analyzed by mean, standard deviation and t - test for dependent groups. The result were shown as follows: The students achievement was significantly higher on the posttest than pretest (p < .01). The students achievement level average on the posttest is Satisfactory level. The students problem-solving ability was significantly higher on the posttest than pretest (p<.01). and The students satisfaction with Inquiry-Based Approach and Polya’s Problem Solving overall is at high level.